Interacting spin 0 fields with torsion via Duffin-Kemmer-Petiau theory - Lunardi, J. T.; Pimentel, B. M.; Teixeira, R. G. (Springer, 2002)
Here we study the behaviour of the spin 0 sector of the DKP field in spaces with torsion. First we show that in a Riemann-Cartan manifold the DKP field presents an interaction with torsion when minimal coupling is performed, contrary to the behaviour of the KO field, a result that breaks the usual equivalence between the DKP and the KG fields.Next we analyse the case of the Teleparallel Equivalent of General Relativity (Weitzenbock manifold), showing that in this case there is a perfect agreement between KG and DKP fields. The origins of both results are also discussed.
Keywords: DKP fields; torsion; Einstein-Cartan theory; teleparallelism